The story as an innovative strategy to promote creativity in primary education - Jaimes Rodríguez, Jhondert Alberto; Ortiz-Ch, Pablo; Navarrete Radilla, María Ysabel; Suárez Carvajal, Lady Andrea; Jaimes Rodríguez, Ledis Albeimar (Emerging Trends in Education, 2024)
The research was carried out under the modality of a feasible project based on a descriptive fieldwork. The population and sample of the study consisted of teaching staff (20) and students (60). The data collection utilized the survey technique through a questionnaire instrument, validated in content through expert judgment. Reliability was determined, resulting in 0.81 for students and 0.82 for teachers, considered very high according to the criteria established by Ruiz (2002). The diagnostic results indicate that the teacher promotes little the realization of theater works or the performance of dramatic games combining body expressions with the narration of a specific story. Likewise, they rarely engage in reading activities using various sounds, noises, and gestures to develop the faculty of imitation in their students. Similarly, it was found that students are interested in practicing recreational reading of stories to enhance their creativity; they are willing to take on recreational reading of stories as an opportunity for personal growth.
Keywords: story; innovative strategy; recreational reading; attitude of schoolchildren; primary education